2023
DOI: 10.1111/jog.15782
|View full text |Cite
|
Sign up to set email alerts
|

The association between weight‐adjusted‐waist index and self‐reported infertility among women of reproductive age in the United States

Qinyuan He,
Chen Chen,
Shufen Bai

Abstract: AimThis study aimed to determine whether the weight‐adjusted‐waist index (WWI) affected infertility in women of childbearing age in the United States.MethodsIn this study, a database from the 2013 to 2018 National Health and Nutrition Examination Survey (NHANES) was used. We analyzed 3374 participants' data cross‐sectionally. The survey used WWI and fertility status as independent and dependent variables. To determine the effect of WWI, an analysis of the independent relationship between WWI and infertility wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Studies have shown that WWI levels were positively linked to an increased risk of infertility in American females and showed a stronger association than other markers of obesity ( 14 ). Although WWI as a central obesity indicator can effectively predict infertility ( 16 ), the relationship between WWI and secondary infertility in women has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that WWI levels were positively linked to an increased risk of infertility in American females and showed a stronger association than other markers of obesity ( 14 ). Although WWI as a central obesity indicator can effectively predict infertility ( 16 ), the relationship between WWI and secondary infertility in women has not been studied before.…”
Section: Introductionmentioning
confidence: 99%